Defining a good death: Perspectives of patients, relatives, and health care professionals in the Catalan context-A qualitative study. - Vicky Serra-Sutton; Lluïsa Fernández-Giner; Mireia Espallargues; Anna García-Altès; in name of the Good death study in Catalonia (PLoS ONE)
Health systems often lack integrated, person-centered end-of-life care. Improving this care is a key priority for decision-makers in the Catalan context. This study aimed to understand how key stakeholders in the healthcare sector-patients, family members, and healthcare professionals-define the concept of a 'good death' and identify their key common elements in Catalonia, Spain. The research team conducted twenty-three semi-structured, in-depth qualitative interviews with patients receiving palliative care or suffering from complex or advanced chronic conditions, older adults over 65 with chronic illnesses, and their relatives. Three-focus discussion groups were also conducted which involved 31 professionals representing care, management, and planning at a local/regional level as well as representatives from patient and family associations involved in end-of-life care. All discussions and interviews followed a predefined guideline, and we recorded and transcribed them for later thematic content and discourse analysis. Overall, participants did not reach a single, universal definition of a 'good death.' Instead, it appears that a 'good death' involves dying in the way each person desires. In our effort to identify common elements, we found that participants consistently mentioned eight: comfort, placidity, safety, warmth, harmony, intimacy, respect, peacefulness and fulfilment. The study provides valuable insights for service planning and enhances the understanding of the needs of individuals at the end of life, including those with chronic conditions and their relatives, as well as the professionals who care for them and manage services or policies at the local and regional levels in Catalonia. The study highlights participants' preferences for their end-of-life care and their views on death, contributing to a broader understanding of what defines a 'good death.'